كتاب سيبويه في دائرة ضوء علم اللّغة الحديث 4ـ المستوى النّحْويّ - يونس, يونس علي (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This comes Search integral part of the series of research thatinvolved under the title (Al Ketab in light of the Department of Modern Linguistics), where she studied in the first part, the curriculum at Sibawayh In the second part, the audio level, and the third morphological level, and in this section I will present a study on the grammar level, which includes rules of grammatical relations in the book Sibawayh (moral clues: the presumption of attribution, customization and specialization, objectivity, question, verbal clues: connectivity, as convergence, toning).Then substitution rules [Description structural rules in the book Sibawayh: replacement, career symmetry. Conversion rules: introduction delays, deletion.And come to the conclusion: The concept of the deep structure of the curriculum Sibawayh than it is in the modern descriptive approach on the one hand that the manufacturing rules of submission and delay, delete and increase, is linking the deep structure and surface structure, highlights our scientific method right at all as laid down in the foundations, and the year of the principles reflect the fact that the descriptive approach, which has a close connection, but to draw attention to benefit from his approach breathes life in Arabic linguistic theory.يأتي هذا البحث متمماً لسلسلة من الأبحاث التي انطوت تحت عنوان (كتاب سيبويه في دائرة ضوء علم اللّغة الحديث )، حيث درست في المبحث الأوّل المنهج عند سيبويه وفي المبحث الثاني المستوى الصوتي، والثالث المستوى الصّرفي، وفي هذا المبحث سأقدم دراسة للمستوى النّحْويّ التي تتضمن قواعد العلاقات النّحْويّة ( القرائن المعنوية: الإسناد، التخصيص، الموضعية، الاستفهام، القرائن اللّفظية: الربط، التضام، التنغيم ).ثم درست قواعد الاستبدال[ قواعد الوصف البنيوي] في كتاب سيبويه التي اشتملت على: الاستبدال، والتماثل الوظيفي. فأما قواعد التحويل فقد تضمنت بمباحث: التقديم والتأخير، الحذف .وتوصلت إلى نتيجة مفادها: إنّ مفهوم البنية العميقة في منهج سيبويه مما هو عليه في المنهج الوصفي الحديث من جهة أنّ القواعد التحويلية من تقديم وتأخير، وحذف وزيادة، هي التي تربط بين البنية العميقة والبنية السطحية، يبرز لنا المنهج العلمي الصائب في كلّ ما أرساه من أسس، وما سنّه من مبادئ تُعبر عن حقيقة منهجه الوصفي الّذي يمتلك صلة وثيقة، وإنّ توجيه النظر إلى الإفادة من منهجه يبعث الحياة في النظرية اللّغوية العربيّة.